Orocutaneous Fistula Formation in Free Flap Reconstruction for Oral Squamous Cell Carcinoma - Qigen Fang (Frontiers in Oncology, 2022)
ObjectiveThe aim of this study is to identify the risk factors associated with orocutaneous fistula (OCF) formation after free flap reconstruction for oral squamous cell carcinoma (SCC).MethodsPatients undergoing free flap reconstruction for oral SCC were retrospectively enrolled. The relationship between clinicopathologic variables and OCF formation was analyzed by univariate and multivariate analyses.ResultsA total of 87 OCFs occurred in 856 patients. Univariate analysis revealed cachexia, tumor at the tongue/floor of the mouth (TFOM), T4 stage, preoperative hemoglobin level, pull-through procedure, preoperative albumin level, and surgical site infection were associated with the formation of OCF. Multivariate analysis confirmed the independence of cachexia, TFOM, T4 stage, and surgical site infection in predicting OCF development. Conventional wound care could achieve successful fistula closure in 82.4% of the patients with a median time of 28 days.ConclusionsOCF formation was common after free flap reconstruction. The presence of cachexia, TFOM tumor site, T4 stage, and surgical site infection significantly increased the risk of OCF formation. Although it required a long period, conventional wound care can obtain satisfactory outcomes in OCF management.